1997
DOI: 10.1097/00007632-199711010-00005
|View full text |Cite
|
Sign up to set email alerts
|

Whiplash Produces an S-Shaped Curvature of the Neck With Hyperextension at Lower Levels

Abstract: In whiplash, the neck forms an S-shaped curvature, with lower level hyperextension and upper level flexion. This was identified as the injury stage for the lower cervical levels. A subsequent C-shaped curvature with extension of the entire cervical spine produced less lower level extension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
109
2
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(122 citation statements)
references
References 12 publications
8
109
2
3
Order By: Relevance
“…Also, after 1 year it was observed that considerable headache was more frequent in the group with traumatic findings (OR 2.8; 95 CI 0. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] and this group had a higher median headache intensity (Table 6). These above mentioned associations were not significant and the group did not differ otherwise from other participants ( Table 7).…”
Section: Associations Between Mri Findings and Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Also, after 1 year it was observed that considerable headache was more frequent in the group with traumatic findings (OR 2.8; 95 CI 0. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] and this group had a higher median headache intensity (Table 6). These above mentioned associations were not significant and the group did not differ otherwise from other participants ( Table 7).…”
Section: Associations Between Mri Findings and Outcomementioning
confidence: 99%
“…This mechanism of injury most often occurs in relation to car collisions, and both in frontal and rear-end impacts the cervical spine is subject to non-physiological stress loading [12,28]. The cardinal symptom following whiplash injuries is neck pain.…”
mentioning
confidence: 99%
“…In an effort to validate the model for rear-end impacts the model has been used to simulate the benchtop trauma sled experiments conducted by Panjabi and co-workers [11,[23][24][25] performed using isolated cervical spine specimens. These studies used cadaveric cervical spine specimens stripped of all non-ligamentous soft tissues mounted to a bench top sled device where an acceleration pulse is applied to the base of the specimen to reproduce whiplash trauma.…”
Section: Simulation Of Whiplashmentioning
confidence: 99%
“…The heads inertia can lead to a situation of high shear in the top of the neck causing overstretching of the ligaments and joint capsules while non-physiological levels of extension in the lower neck can have potentially damaging effects on the anterior soft tissues. Many of the soft-tissue components of the neck have been identified as possible injury sites [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Various anatomical structures have been identified as potential injury sites, with many recent investigations focusing on the facet joint [1,7,19,21]. In vivo and in vitro studies have shown that the lower cervical spine hyperextends during the initial phase of whiplash [12,18]. While hyperextension may cause facet joint compression injuries, it may also result in excessive strains in the anterior soft tissues [32].…”
Section: Introductionmentioning
confidence: 99%